Working towards development of a sustainable brucellosis control programme, the Azerbaijan example. (July 2021) - Khatibi, Masud; Abdulaliyev, Galib; Azimov, Anar; Ismailova, Rita; Ibrahimov, Sabina; Shikhiyev, Mazahir; Agalarov, Dilgam; Seyidov, Tural; Omarov, Asaf; Suleymanova, Chichak; Zeynalova, Shalala; Abdullayev, Rakif; et al.
Abstract: Brucellosis caused by Brucella abortus and Brucella melitensis is endemic in the Republic of Azerbaijan but a complex mix of fiscal, political and technical constraints has impeded regulatory authority decision making for adoption of a sustainable national control programme. This paper reports a series of epidemiologic studies of the disease in animals and humans which we conducted between 2009 and 2020. A preliminary study and a subsequent larger study using vaccination of all non-pregnant female sheep and goats of breeding age and all females between 3 and 8 months with conjunctival Rev1 vaccine both recorded significant reduction in small ruminant seroprevalences. A case control study of winter pasture flocks found many case and control farmers used raw milk to make dairy products for sale, ate fresh cheese and sold dairy products in unregulated markets. Almost all farmers expressed willingness to pay a portion of the costs associated with elimination of brucellosis from their flocks. A pilot human study in 2009 led to a large study in 2017 which recorded an overall seroprevalence of 8.1% in humans. Persons in farm related occupations were at greater risk than urban persons and males were more likely to be seropositive than females. Risk factors included keeping small ruminants, using raw milk cheese and slaughtering animals whereas having heard education information about brucellosis and vaccinating against brucellosis were protective. Highlights: Well designed and well conducted brucellosis control programmes deliver good outcomes in low income countries. A One Health approach is appropriate for brucellosis control. Quality assurances for vaccines, tests and vaccination are essential components. Reliable data are required for decision making. Identification of vaccinates is required for assessment of coverage.